The Inclusion–Dependency Paradox: Platform-Orchestrated SME Participation and Asymmetric Value Capture in the ASEAN Digital Economy - Bambang Subeno (Manexia: Journal of Business, Management, and Creative Economy, 2025)
Platform ecosystems have become central infrastructures for small and medium-sized enterprise (SME) participation in emerging digital economies. While platform-mediated inclusion is widely associated with opportunity expansion, its structural consequences for autonomy and surplus distribution remain under-theorized. This article develops the concept of the Inclusion–Dependency Paradox to explain how platform-orchestrated SME participation simultaneously enhances value creation and intensifies structural dependence. Integrating platform ecosystem theory, resource dependence logic, value creation–value capture distinctions, and embeddedness scholarship, the analysis proposes a mechanism-based framework linking governance centralization, control over critical resources, and asymmetric value capture. Platform inclusion lowers entry barriers and expands market access, thereby increasing SME value creation capacity. However, concentrated control over algorithmic visibility, transactional infrastructure, and data flows reconfigures bargaining asymmetries and shapes surplus allocation. The model specifies a curvilinear relationship between inclusion and autonomy, suggesting that high levels of participation under centralized governance conditions amplify dependency risks. By reframing inclusion as structurally contingent rather than inherently empowering, this study advances a distribution-sensitive perspective on SME participation in digitally mediated markets.